Melatonin protects against streptozotocin-induced diabetic cardiomyopathy by the phosphorylation of vascular endothelial growth factor-A (VEGF-A) - Behram Kandemir, Yasemin; Guntekin, íœnal; Tosun, Veysel; Korucuk, Necmettin; Bozdemir, Mehmet Nuri (Cellular and Molecular Biology, 2018)
The aim of the present study is to investigate if the melatonin has any protective effect on diabetic cardiomyopathy and antioxidant enzymes via phosphorylation of vascular endothelial growth factor-A (VEGF-A). A total of 40 male Wistar rats were enrolled in the study. Rats were divided into four groups: group 1 (control, n=10), group 2 (DM, n=10), group 3 (melatonin, n=10), and group 4 (melatonin+DM, n=10). Melatonin was injected intraperitoneally at a dose of 50 mg/kg/day for 56 days to group 3 and group 4. We investigated expression and phosphorylation of the VEGF-A in coronary vessels of all groups. Staining intensities, biochemical, immunohistochemistry analysis, and transthoracic echocardiography were performed. In comparison to the group 1, DM induced a decrease in p-VEGF-A in coronary vessels of group 2. The lower constitutive phosphorylation of VEGF-A in the group 2 was also increased in coronary vessels after melatonin treatment (p<0.05). Diabetic rats developed myocardial hypertrophy with preserved cardiac function (p<0.05). Cardio-protective effect of melatonin may reduce the damages of diabetes mellitus on the heart muscle fibers and coronary vessels via the phosphorylation of VEGF-A. Melatonin-dependent phosphorylation of VEGF-A in coronary angiogenesis may be associated with the physiological as well as with the pathological cardiac hypertrophy.